(untitled) (Journal of Universal Science Research, 2023)
Security is the most essential element of every sovereign country. Nowadays there are a lot of international and local crimes in the life of society. Such as terrorism, criminal and extremist activities. They are the most hazardous. As well as every kind of countries try to get more safe and powerful police system. OPERATIONAL-SEARCH ACTIVITY is the main and basic part of the Ministry of Internal Affairs. In this article, we discuss some types of principles and elements of operational-search activity.